2014
DOI: 10.3386/w20760
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Bank Opacity

Abstract: Did regulatory reforms that lowered barriers to competition among U.S. banks increase or decrease the degree to which banks manage the information that they disclose to the public and regulators? We find that relaxing regulatory impediments to competition reduced discretionary loan loss provisioning and the frequency with which banks restate financial statements. The results suggest that competition reduces bank opacity, enhancing the ability of markets and regulators to monitor banks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 8 publications
(12 reference statements)
1
27
0
Order By: Relevance
“…Increasing bank competition is found to decrease bank opacity and banks disclose more information in competitive markets (Jiang et al, 2016). Greater competition may thus increase bank stability as competition also disciplines banks to increase monitoring and/or improve their selection of borrowers (Diamond, 1984).…”
Section: Banking Deregulation Gradually Lifted Bank Entry Restrictionmentioning
confidence: 99%
See 3 more Smart Citations
“…Increasing bank competition is found to decrease bank opacity and banks disclose more information in competitive markets (Jiang et al, 2016). Greater competition may thus increase bank stability as competition also disciplines banks to increase monitoring and/or improve their selection of borrowers (Diamond, 1984).…”
Section: Banking Deregulation Gradually Lifted Bank Entry Restrictionmentioning
confidence: 99%
“…Earlier work found that the deregulation of interstate banking and branching restrictions improved transparency (Jiang et al, 2016) and efficiency (Stiroh and Strahan, 2003) of the banking sector, enabled banks to enjoy benefits of geographic diversification (Goetz et al, 2016), spurred economic growth (Jayaratne and Strahan, 1996) and reduced inequality at the state level (Beck et al, 2010 …”
Section: Interstate Banking Deregulation and Entry Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Larger absolute values of these residuals indicate greater earnings opacity. In additional tests, we use signed measures to capture whether discretionary provisioning is used to increase or decrease earnings, because managers have incentives to overstate earnings (Huizinga and Laeven (2012); Norden and Stoian (2014); Jiang et al (2016)).…”
mentioning
confidence: 99%